PERBANDINGAN UJI KUAT TEKAN BETON K-200 DAN SUBTITUSI SERBUK TEMPURUNG KELAPA TERHADAP BETON NORMAL - Syamsuddin, Muhammad Sandy; Hamsyah; Muhammad Jabir (Fakultas Teknik Universitas Muhammadiyah Parepare, 2023)
The strength of concrete is determined by the characteristics of the material it forms and its density. Coconut shell is an organic waste that exists all around us and its use is mostly limited to fuelwood. This is the rationale for utilizing coconut shells as a fine aggregate additive in the manufacture of concrete. This study aims to determine the characteristics of the material and the comparison of the compressive strength of concrete as a substitute for fine aggregate. In this study using experimental methods according to SNI standards by comparing all variations. The results of the compressive strength test at the age of 28 days on normal concrete were 201.07 Kg/cm2, 15% variation of 152.76 Kg/cm2, and 30% variation of 148.27 Kg/cm2, indicating that the addition or replacement of fine aggregate using coconut shell powder in the concrete mixture has decreased and the results of testing the characteristics of the material do not meet the requirements according to the standards so that the research results cannot be used.